1999
DOI: 10.1103/physrevb.59.12678
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiostructural, elastic, and vibrational properties of carbon nanotubes

Abstract: A study based on ab initio calculations is presented on the structural, elastic, and vibrational properties of single-wall carbon nanotubes with different radii and chiralities. These properties are obtained using an implementation of pseudopotential-density-functional theory which allows calculations on systems with a large number of atoms per cell. Different quantities are monitored versus tube radius. The validity of expectations based on graphite is explored down to small radii, where some deviations appea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

92
528
3
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 914 publications
(628 citation statements)
references
References 59 publications
92
528
3
5
Order By: Relevance
“…The E value of 0.25 TPa is remarkably high for a 2D membrane and approaches that predicted for pristine graphene. 25 At the same time, this value provides a boundary for the maximum mechanical performance that could be reached via optimization of the interlayer coupling within bulk, paper-like materials based on (reduced) GO. 14 From Figure 5a, it can be seen that the conductivity of the reduced GO sheets scales inversely with the elastic modulus.…”
mentioning
confidence: 99%
“…The E value of 0.25 TPa is remarkably high for a 2D membrane and approaches that predicted for pristine graphene. 25 At the same time, this value provides a boundary for the maximum mechanical performance that could be reached via optimization of the interlayer coupling within bulk, paper-like materials based on (reduced) GO. 14 From Figure 5a, it can be seen that the conductivity of the reduced GO sheets scales inversely with the elastic modulus.…”
mentioning
confidence: 99%
“…As a result, the 2-D graphene phonon modes are further split into a large number of sub-bands. If the SWCNT contains N atoms per unit cell, there are 3N phonon modes in total, many of which are degenerated [26]. As the simulated SWCNT consisted of 36 atoms, total 108 phonon modes were obtained.…”
Section: Vibrational Modesmentioning
confidence: 99%
“…The ab initio approach is advantageous because such calculations do not depend on any predefined parameter. There are different authors that have reported ab initio phonon dispersion of SWCNT's, all using the super cell approach [26][27][28].The largest differences between ab initio calculations and zone-folding occur in the low frequency range and for tubes with small diameters (less than 0.7 nm) also in the high frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…Continuum elastic shell models [26][27][28][29][30][31] used to study RBM vibration of SWCNTs do not consider scale effects. Also, atomistic methods [32][33][34] which do consider scale effects are costly and time consuming to implement particularly for large-scale systems.…”
Section: Introductionmentioning
confidence: 99%